Modelling land use planning: Socioecological integrated analysis of metropolitan green infrastructures. (March 2023) - Marull, Joan; Padró, Roc; La Rota-Aguilera, María José; Pino, Joan; Giocoli, Annalisa; Cirera, Jacob; Ruiz-Forés, Núria; Coll, Francesc; Serrano-Tovar, Tarik; Velasco-Fernández, Raúl
Abstract: Land use planning of global metropolis is essential to meet the socioecological challenges of the next decades. This paper aims to contribute to sustainable land use policies by proposing a socioecological integrated analysis of metropolitan green infrastructures, applying this landscape-metabolism model to the Urban Master Plan of the Barcelona Metropolitan Area. The paper assesses the multiple functions and services of the green infrastructure in four land use scenarios and two types of agricultural management. The results show that the trending scenario of applying the current land use planning would have a negative impact in the ecological functioning of the landscape, affecting biodiversity and the provision of ecosystem services to society. The results also show that certified organic farming is not enough to overcome some trends of industrial agriculture as low energy efficiency or greenhouse gas emissions. Finally, the results show different interactions between social metabolism and landscape ecology, as changes in the form of metabolism affect the functioning of the landscape, while changes in land cover specially affect resource use. Therefore, deeper changes are needed in land use policies that consider not only land covers, as has traditionally been done, but also metabolic flows to promote agroecological transitions towards more sustainable metropolitan green infrastructures under climate change scenarios. Graphical Abstract: ga1 Highlights: Socioecological integrated analysis of metropolitan green infrastructure is proposed. Functions and services in land use and agriculture management scenarios are assessed. Metabolism affects landscape function, while land cover change affects resource use. Certified organic farming is not enough to overcome impact of industrial agriculture. Policies should apply landscape-metabolic models towards agroecological transition.